A fast-charging and fast-discharging lithium battery and preparation method thereof
By using carbon fluorinated carbon nanotubes prepared with biomass carbon and two-dimensional hierarchical porous composite materials loaded with cerium oxide in lithium batteries, the problem of insufficient charging efficiency and discharge power density in the fast charging and discharge process of traditional lithium batteries is solved. Improves the cycle stability and safety of the battery and achieves more efficient electrochemical performance.
Patent Information
- Application Number
- CN202411652010.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-19
AI Technical Summary
Traditional lithium batteries have charging efficiency limitations, insufficient discharge power density, cycle stability and safety problems during fast charging and discharging, resulting in shortening of battery life and safety hazards.
Fast-charge and fast-discharge lithium batteries are prepared by using fluorinated carbon nanotubes and cerium-loaded two-dimensional graded porous composite materials based on biomass carbon, combined with eutectic and dendritic mesoporous silica nanoparticles, and prepared by improving electrodes The structure and chemical properties of the material improve ion transfer rate and the mechanical strength of the electrode.
It improves the migration smoothness of lithium ions and the charging and discharging performance of the battery, extends the cycle life of the battery, enhances structural stability and safety, and adapts to high-rate charging and discharging conditions.
Smart Images

Figure CN119153803B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery preparation, and in particular to a fast-charge and fast-discharge lithium battery and a preparation method thereof. Background Art
[0002] With the popularization of portable electronic devices and the rapid development of the new energy vehicle industry, the market demand for high-performance batteries is growing, especially emphasizing the fast charging capability and high-power discharge performance of batteries. Although traditional lithium batteries have made significant progress in energy density, they still face many challenges in fast charging and fast discharging performance, which are mainly reflected in the following aspects:
[0003] Charging efficiency limitation: In existing lithium battery technology, the fast charging process can easily cause the internal temperature of the battery to rise sharply, which not only affects the battery life, but may also cause safety issues. In addition, under high current density, the diffusion rate of lithium ions in the electrode material becomes a key factor limiting the fast charging rate.
[0004] Discharge power density: High-power discharge often encounters the problem of rapid voltage drop, which affects the continuous operation time and performance of the equipment. This is mainly because the electronic conductivity and ion diffusion rate of the electrode material are not enough to support the high-intensity discharge requirements.
[0005] Cycle stability and safety: Fast charge and discharge cycles can easily accelerate the degradation of the battery's internal structure, leading to faster capacity decay. At the same time, it may cause safety hazards such as internal short circuits and thermal runaway.
[0006] Therefore, we propose a fast-charge and fast-discharge lithium battery and a preparation method to solve the above problems. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a fast-charge and fast-discharge lithium battery and a preparation method thereof.
[0008] A method for preparing a fast-charge and fast-discharge lithium battery comprises the following steps:
[0009] S1: Preparation of fluorinated carbon nanotubes based on biomass carbon
[0010] Preparation of tubular biomass carbon by cattail fluff, followed by nitrogen doping of the tubular biomass carbon to obtain nitrogen-doped carbon nanotubes, acidification of the nitrogen-doped carbon nanotubes and subsequent fluorine doping to obtain fluorinated carbon nanotubes;
[0011] S2: Preparation of positive electrode sheet
[0012] A eutectic is prepared by coronene and NDI-1, and a positive electrode plate is prepared by using the eutectic, carbon black, fluorinated carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone as raw materials;
[0013] S3: Preparation of dendritic mesoporous silica nanoparticles
[0014] Dendritic mesoporous silica nanoparticles are obtained by a synthetic reaction using triethanolamine, cetyltrimethylammonium bromide, sodium salicylate, tetraethyl silicate and ethanol as raw materials.
[0015] S4: Preparation of two-dimensional hierarchical porous composites loaded with cerium oxide
[0016] Dendritic mesoporous silica nanoparticles, zinc acetate dihydrate and cerium nitrate hexahydrate were mixed and calcined to prepare a composite precursor, and then a two-dimensional hierarchical porous composite material loaded with cerium oxide was prepared by regulating with a 2-methylimidazole solution and a sodium dodecyl sulfate solution;
[0017] S5: Preparation of negative electrode sheet
[0018] A positive electrode sheet is prepared by using a two-dimensional hierarchical porous composite material loaded with cerium oxide, carbon black, fluorinated carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone as raw materials;
[0019] S6: Assembly of lithium batteries
[0020] The positive electrode sheet, the negative electrode sheet, the separator and the electrolyte are assembled to prepare a lithium battery.
[0021] Furthermore, step S1 is to prepare fluorinated carbon nanotubes based on biomass carbon, which specifically includes the following steps:
[0022] S1.1: Wash the cattail fluff with deionized water for 2-3 times, soak the washed cattail fluff in anhydrous ethanol for 20-30 minutes, and then dry it in an oven at 110-120°C. Add 2-3 parts by weight of the dried cattail fluff to 230-240 parts by weight of 0.5M H 3 PO 4 The solution was stirred for 1-2 hours and then allowed to stand for 24-25 hours, the supernatant was removed, the precipitate was dried at 110-120°C, placed in a tubular furnace filled with nitrogen, heated to 650-670°C at 5-8°C / min, calcined for 2-3 hours, ground and crushed after cooling, then washed with deionized water 2-3 times, and freeze-dried for 10-12 hours to obtain tubular biomass carbon;
[0023] S1.2: dissolving 2-3 parts by weight of dicyandiamide and 1-2 parts by weight of nickel nitrate in 250-300 parts by weight of ethanol solution, stirring at 78-80° C. for 5-8 hours, then adding 0.2-0.5 parts by weight of tubular biomass carbon, and continuing stirring for 24-25 hours to obtain a mixed solution;
[0024] S1.3: placing the mixed solution in a quartz tube furnace, heating to 1000-1100°C at 5-8°C / min in a nitrogen atmosphere, calcining and keeping warm for 1-2h, placing the black product obtained by calcination in a 5-7mol / L sulfuric acid solution, stirring at 80-85°C for 8-10h, then washing with deionized water until neutral, and vacuum drying to obtain nitrogen-doped carbon nanotubes;
[0025] S1.4: immersing 1-2 parts by weight of nitrogen-doped carbon nanotubes in the mixed solution, ultrasonicating for 1-2 hours, and leaving at room temperature for 10-12 hours, then washing with deionized water until neutral, and vacuum drying at 80-90° C. for 20-24 hours to obtain acidified nitrogen-doped carbon nanotubes;
[0026] S1.5: Add 1 mol / L KOH-ethanol solution to 2-3 parts by weight of 14 wt% perfluorosulfonic acid resin-ethanol dispersion, adjust the pH value of the resin dispersion to neutral, and obtain a perfluorosulfonic acid resin ethanol dispersion. Mix the acidified nitrogen-doped carbon nanotubes with the perfluorosulfonic acid resin ethanol dispersion in a mass ratio of 70-80:5-30, grind them in a mortar evenly, and then transfer them to a tubular furnace filled with nitrogen for calcination, raise the temperature to 480-500°C at 5-8°C / min, and keep them warm for 10-12h to obtain fluorinated carbon nanotubes.
[0027] Furthermore, step S2 of preparing the positive electrode sheet specifically includes the following steps:
[0028] S2.1: Coronene and NDI-1 were mixed and dissolved in dichloroethane at a molar ratio of 1:1 to a concentration of 6-7 mg / mL. The mixed solution was divided into centrifuge tubes, the speed was set to 11000-12000 rpm, and centrifuged for 30-40 min. The precipitate was cleaned with anhydrous ethanol, collected and dried to obtain the co-crystal;
[0029] S2.2: 8-10 parts by weight of eutectic, 1-2 parts by weight of carbon black, 1-2 parts by weight of fluorinated carbon nanotubes and 1-2 parts by weight of polyvinylidene fluoride are mixed and ground for 10-12 minutes, the ground mixed powder is transferred to a beaker, 10-20 parts by weight of N-methylpyrrolidone is added under magnetic stirring, the beaker is sealed with a sealing film, and the mixture is stirred for 12-14 hours to form a slurry;
[0030] S2.3: Use a scraper to evenly apply the slurry on the aluminum foil, then put the aluminum foil into a vacuum drying oven at 80-90°C and dry it for 12-14 hours. After drying, the aluminum foil is sliced with a slicer to prepare a positive electrode sheet.
[0031] Furthermore, step S3 of preparing dendritic mesoporous silica nanoparticles specifically comprises the following steps:
[0032] S3.1: adding 0.3-0.5 parts by weight of triethanolamine to 200-300 parts by weight of deionized water, heating to 80-85°C and stirring for 30-40 minutes, then adding 5-8 parts by weight of cetyltrimethylammonium bromide and 3-5 parts by weight of sodium salicylate, stirring and mixing for 1-2 hours to obtain a mixed solution;
[0033] S3.2: Mix 30-40 parts by weight of tetraethyl orthosilicate and 3-5 parts by weight of ethanol, add the mixture to the mixed solution, stir and react for 3-4 hours, then centrifuge at 2000-3000 r / min for 10-12 minutes, wash the precipitate after centrifugation with ethanol 2-3 times, and then calcine at 500-550°C for 6-8 hours to obtain dendritic mesoporous silica nanoparticles.
[0034] Furthermore, step S4 of preparing the two-dimensional hierarchical porous composite material loaded with cerium oxide specifically comprises the following steps:
[0035] S4.1: Disperse 0.15-0.2 parts by weight of dendritic mesoporous silica nanoparticles in 10-12 parts by weight of ethanol, then add 0.2-0.3 parts by weight of zinc acetate dihydrate and 0.1-0.2 parts by weight of cerium nitrate hexahydrate, stir and mix at room temperature for 10-12 hours, then evaporate to dryness at 40-45° C., and calcine the obtained powder at 400-450° C. for 3-5 hours to obtain a composite precursor;
[0036] S4.2: dissolving 0.3-0.5 parts by weight of 2-methylimidazole in 10-12 parts by weight of deionized water, and dispersing by ultrasonic for 1-2 minutes to obtain a 2-methylimidazole solution; dissolving 0.1-0.2 parts by weight of sodium dodecyl sulfate in 10-12 parts by weight of deionized water, and dispersing by ultrasonic for 1-2 minutes to obtain a sodium dodecyl sulfate solution;
[0037] S4.3: Add 0.5-1 parts by weight of the composite precursor to the sodium dodecyl sulfate solution, then add the 2-methylimidazole solution, stir and mix for 10-15 seconds, seal the mixture in a strain bottle, react at 26-28°C for 20-24 hours, and then centrifuge at 7000-8000 r / min to obtain a reaction product;
[0038] S4.4: The reaction product is washed with methanol for 2-3 times, and then washed with deionized water for 2-3 times, and then placed in ethanol for 20-24 hours. Finally, the reaction product is dried to obtain a two-dimensional hierarchical porous composite material loaded with cerium oxide.
[0039] Furthermore, step S5 of preparing the negative electrode sheet specifically includes the following steps:
[0040] S5.1: 8-10 parts by weight of a two-dimensional hierarchical porous composite material loaded with cerium oxide, 3-4 parts by weight of carbon black, 1-2 parts by weight of carbon nanotubes and 1-2 parts by weight of polyvinylidene fluoride are mixed and ground for 10-12 minutes, the ground mixed powder is transferred to a beaker, 10-20 parts by weight of N-methylpyrrolidone is added under magnetic stirring, the beaker is sealed with a sealing film, and the mixture is stirred for 12-14 hours to form a slurry;
[0041] S5.2: Use a scraper to evenly apply the slurry on the copper foil, then put the copper foil into a vacuum drying oven at 80-90°C and dry it for 12-14 hours. After drying, the copper foil is sliced with a slicer to prepare a negative electrode sheet.
[0042] Furthermore, step S6 of assembling the lithium battery specifically includes the following steps:
[0043] S6.1: The positive electrode sheet, the negative electrode sheet, and the coated separator are formed into a battery cell by using a Z-shaped stacking structure, wherein the positive and negative electrode tabs of the stacking are located on the opposite sides of the battery cell, and the outermost circle of the stacking body is terminated by the negative electrode sheets on the upper and lower sides of the battery cell body, thereby obtaining a battery cell body;
[0044] S6.2: The battery cell is prepared into a lithium-ion battery through the processes of baking, ultrasonic welding, top-side packaging, baking, electrolyte injection, static, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0045] Furthermore, the mixed solution in step S1.4 is obtained by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3-4.
[0046] Furthermore, in step S6.1, the diaphragm is a Celgard 2400 polymer diaphragm.
[0047] A fast-charge and fast-discharge lithium battery is prepared by any of the above-mentioned methods for preparing a fast-charge and fast-discharge lithium battery.
[0048] Compared with the prior art, the present invention has at least the following beneficial effects:
[0049] 1. The present invention prepares a eutectic and adds it to the preparation of the positive electrode pole piece of the battery. The eutectic has a loose skeleton, in which a large number of gaps provide an effective transportation path for the embedding and de-embedding of lithium ions, making the migration of lithium ions in the electrode smoother, reducing the transmission resistance, and increasing the ion transmission rate, thereby improving the charge and discharge performance of the battery, especially under high-rate charge and discharge conditions, which can effectively reduce the polarization phenomenon of the battery and improve the power output of the battery. The loose skeleton structure can also increase the contact area between the electrode and the electrolyte, so that more lithium ions can participate in the reaction, further improving the capacity and energy density of the battery.
[0050] 2. The present invention adds fluorinated carbon nanotubes and eutectics in the preparation of the positive electrode plate of the battery. The loose skeleton of the eutectic can buffer the volume change caused by the insertion and deinsertion of lithium ions. The fluorinated carbon nanotubes have high conductivity and good mechanical strength, and can form a conductive network in the electrode to provide a fast channel for the transmission of lithium ions and electrons. At the same time, it can serve as a supporting structure to enhance the mechanical strength of the electrode, and can withstand the stress generated by the electrode during the charging and discharging process to prevent the electrode from deforming and rupturing. The large number of lithium ion transmission paths provided by the eutectic and the high conductivity of the fluorinated carbon nanotubes can increase the reversible capacity of the electrode. The composite of the eutectic and the fluorinated carbon nanotubes can reduce the internal resistance of the battery and reduce the heat generated by the battery during the charging and discharging process. Therefore, the synergistic effect of the eutectic and the fluorinated carbon nanotubes can improve the capacity and cycle life of the electrode, while enhancing the structural stability of the electrode and improving the performance and safety of the battery.
[0051] 3. The present invention uses dendritic mesoporous silica nanoparticles as a silicon substrate, loads a metal organic framework therein, and uses sodium dodecyl sulfate as a directing agent soft template for precise control to prepare a two-dimensional hierarchical porous composite material and load cerium oxide on it. Mesoporous silica itself has good chemical stability and mechanical stability. During the battery charging and discharging process, it can withstand the volume change of the electrode material and reduce the pulverization and shedding of the material. During the synthesis of the composite material, the hydrophilic group and hydrophobic group of sodium dodecyl sulfate can interact with different reactants respectively, so that the material grows in a two-dimensional direction to form a two-dimensional layered structure, which can make ions diffuse more easily between layers. Compared with the disordered structure, the transmission path of ions in the two-dimensional layered structure is more regular and shorter, thereby improving the fast charging performance of the battery. When the battery is overcharged or over-discharged, the loaded cerium oxide can adjust the charge state of the electrode surface through its own redox reaction, inhibit the structural damage of the electrode material, and thus improve the cycle stability of the battery.
[0052] 4. The present invention prepares fluorinated carbon nanotubes through cattail fluff. Cattail fluff is a natural material with a large number of voids and micropores in its fiber structure. The natural structure of cattail fluff helps to simplify the preparation process of fluorinated carbon nanotubes and reduce energy consumption. At the same time, the fiber structure of cattail fluff can serve as a natural template to help form a uniformly distributed porous structure, and the porous structure helps to increase the specific surface area of fluorinated carbon nanotubes, thereby increasing the migration and diffusion rate of lithium ions, and effectively increases the electrochemical reaction active area in contact with the electrolyte, thereby improving the electronic conductivity and ionic conductivity of the battery.
[0053] 5. The present invention prepares nitrogen-doped carbon nanotubes and then performs acidification. The acidification process can cause defects on the surface of the carbon tubes and introduce functional groups such as hydroxyl and carboxyl groups to perform fluorine atom doping, thereby achieving dual doping of nitrogen atoms and fluorine atoms. Nitrogen doping can improve the conductivity of the carbon nanotubes. The strong electronegativity of fluorine atoms can also improve the conductivity of the carbon nanotubes. At the same time, the fluorine-containing carbon surface with higher polarity has stronger affinity and wettability for the electrolyte, which can promote better penetration of the electrolyte, making the migration channel of lithium ions between the electrode and the electrolyte more unobstructed, reducing the resistance in the ion transmission process, and lithium ions can move more quickly between the positive and negative electrodes, thereby improving the charge and discharge rate and power performance of the battery, which is beneficial to the fast charge and discharge of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.
[0055] Figure 1 This is a flow chart of a method for preparing a fast-charge and fast-discharge lithium battery used in an embodiment of the present invention. DETAILED DESCRIPTION
[0056] The following is a detailed description of a method for preparing a fast-charge and fast-discharge lithium battery provided by the present invention in conjunction with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.
[0057] NDI-1 structure:
[0058]
[0059] Coronene structure:
[0060]
[0061] Eutectic single crystal structure:
[0062]
[0063] Example 1
[0064] A method for preparing a fast-charge and fast-discharge lithium battery, such as Figure 1 As shown, the following steps are included:
[0065] S1: Preparation of fluorinated carbon nanotubes based on biomass carbon
[0066] S1.1: The cattail fluff was washed twice with deionized water, soaked in anhydrous ethanol for 20 min, and then dried in an oven at 120°C. 2 parts by weight of the dried cattail fluff was added to 230 parts by weight of 0.5 M H 3 PO 4 The solution was stirred for 1 hour and then allowed to stand for 24 hours. The supernatant was removed, and the precipitate was dried at 110°C, placed in a tubular furnace filled with nitrogen, and heated to 650°C at 5°C / min, calcined for 2 hours, ground and crushed after cooling, and then washed twice with deionized water and freeze-dried for 10 hours to obtain tubular biomass carbon.
[0067] S1.2: 2 parts by weight of dicyandiamide and 1 part by weight of nickel nitrate are dissolved in 250 parts by weight of ethanol solution, stirred at 78° C. for 5 hours, then 0.2 parts by weight of tubular biomass carbon are added, and stirring is continued for 24 hours to obtain a mixed solution;
[0068] S1.3: The mixed solution was placed in a quartz tube furnace, and the temperature was raised to 1000°C at 5°C / min in a nitrogen atmosphere, and the mixture was calcined and kept warm for 1 hour. The black product obtained by calcination was placed in a 5 mol / L sulfuric acid solution, and stirred at 80°C for 8 hours. The mixture was then washed with deionized water until neutral, and vacuum dried to obtain nitrogen-doped carbon nanotubes.
[0069] S1.4: immersing 1 part by weight of nitrogen-doped carbon nanotubes in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3, ultrasonicating for 1 hour, and leaving at room temperature for 10 hours, then washing with deionized water until neutral, and vacuum drying at 80°C for 20 hours to obtain acidified nitrogen-doped carbon nanotubes;
[0070] S1.5: Add 1 mol / L KOH-ethanol solution to 2 parts by weight of 14 wt% perfluorosulfonic acid resin-ethanol dispersion, adjust the pH value of the resin dispersion to neutral, and obtain a perfluorosulfonic acid resin ethanol dispersion. Mix the acidified nitrogen-doped carbon nanotubes with the perfluorosulfonic acid resin ethanol dispersion in a mass ratio of 70:5, grind them in a mortar and grind them evenly. Then, transfer them to a tubular furnace filled with nitrogen and calcine them. Raise the temperature to 480°C at 5°C / min and keep them warm for 10 hours to obtain fluorinated carbon nanotubes.
[0071] S2: Preparation of positive electrode sheet
[0072] S2.1: Coronene and NDI-1 were mixed and dissolved in dichloroethane at a molar ratio of 1:1 to a concentration of 6 mg / mL. The mixed solution was divided into centrifuge tubes, set the speed to 11000 rpm, and centrifuged for 30 min. The precipitate was cleaned with anhydrous ethanol, collected and dried to obtain the co-crystal;
[0073] S2.2: 8 parts by weight of eutectic, 1 part by weight of carbon black, 1 part by weight of fluorinated carbon nanotubes and 1 part by weight of polyvinylidene fluoride were mixed and ground for 10 minutes, the ground mixed powder was transferred to a beaker, 10 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 12 hours to form a slurry;
[0074] S2.3: Use a scraper to evenly apply the slurry on the aluminum foil, then put the aluminum foil into a vacuum drying oven at 80°C for 12 hours, and slice the dried aluminum foil with a slicer to prepare a positive electrode sheet;
[0075] S3: Preparation of dendritic mesoporous silica nanoparticles
[0076] S3.1: 0.3 parts by weight of triethanolamine is added to 200-300 parts by weight of deionized water, and then heated to 80-85° C. and stirred for 30-40 minutes, and then 5-8 parts by weight of cetyltrimethylammonium bromide and 3-5 parts by weight of sodium salicylate are added, and the mixture is stirred for 1-2 hours to obtain a mixed solution;
[0077] S3.2: 30-40 parts by weight of tetraethyl orthosilicate and 3-5 parts by weight of ethanol are mixed and added to the mixed solution, and the mixture is stirred for reaction for 3-4 hours, and then centrifuged at 2000-3000 r / min for 10-12 minutes, and the precipitate after centrifugation is washed with ethanol 2-3 times, and then calcined at 500-550° C. for 6-8 hours to obtain dendritic mesoporous silica nanoparticles;
[0078] S4: Preparation of two-dimensional hierarchical porous composites loaded with cerium oxide
[0079] S4.1: 0.15 parts by weight of dendritic mesoporous silica nanoparticles are dispersed in 10 parts by weight of ethanol, and then 0.2 parts by weight of zinc acetate dihydrate and 0.1 parts by weight of cerium nitrate hexahydrate are added, and the mixture is stirred and mixed at room temperature for 10 hours, and then evaporated at 40°C, and the obtained powder is calcined at 400°C for 3 hours to obtain a composite precursor;
[0080] S4.2: 0.3 parts by weight of 2-methylimidazole was dissolved in 10 parts by weight of deionized water, and ultrasonic dispersion was performed for 1 minute to obtain a 2-methylimidazole solution; 0.1 parts by weight of sodium dodecyl sulfate was dissolved in 10 parts by weight of deionized water, and ultrasonic dispersion was performed for 1 minute to obtain a sodium dodecyl sulfate solution;
[0081] S4.3: Add 0.5 parts by weight of the composite precursor to the sodium dodecyl sulfate solution, then add the 2-methylimidazole solution, stir and mix for 10 seconds, seal the mixture in a strain bottle, react at 26°C for 20 hours, and then centrifuge at 7000 r / min to obtain a reaction product;
[0082] S4.4: washing the reaction product twice with methanol, then washing it twice with deionized water, and then keeping it in ethanol for 20 hours. Finally, drying the reaction product to obtain a two-dimensional hierarchical porous composite material loaded with cerium oxide;
[0083] S5: Preparation of negative electrode sheet
[0084] S5.1: 8 parts by weight of a two-dimensional hierarchical porous composite material loaded with cerium oxide, 3 parts by weight of carbon black, 1 part by weight of carbon nanotubes and 1 part by weight of polyvinylidene fluoride were mixed and ground for 10 minutes, the ground mixed powder was transferred to a beaker, 10 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 12 hours to form a slurry;
[0085] S5.2: Use a scraper to evenly apply the slurry on the copper foil, then put the copper foil into a vacuum drying oven at 80° C. and dry it for 12 h. After drying, the copper foil is sliced with a slicer to prepare a negative electrode sheet;
[0086] S6: Assembly of lithium batteries
[0087] S6.1: The positive electrode sheet, the negative electrode sheet, and the Celgard2400 polymer separator are formed into a battery cell by using a Z-shaped stacking structure, wherein the positive and negative electrode tabs of the stack are located on the opposite sides of the battery cell, and the outermost circle of the stack body is terminated by the negative electrode sheets on the upper and lower sides of the battery cell body, thereby obtaining a battery cell body;
[0088] S6.2: The battery cell is prepared into a lithium-ion battery through the processes of baking, ultrasonic welding, top-side packaging, baking, injection of lithium hexafluorophosphate electrolyte, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0089] Example 2
[0090] A method for preparing a fast-charge and fast-discharge lithium battery, such as Figure 1 As shown, the following steps are included:
[0091] S1: Preparation of fluorinated carbon nanotubes based on biomass carbon
[0092] S1.1: The cattail fluff was washed twice with deionized water, soaked in anhydrous ethanol for 20 min, and then dried in an oven at 110°C. 3 parts by weight of the dried cattail fluff was added to 240 parts by weight of 0.5 M H 3 PO 4 The solution was stirred for 1 hour and then allowed to stand for 24 hours. The supernatant was removed, and the precipitate was dried at 110°C, placed in a tubular furnace filled with nitrogen, and heated to 650°C at 5°C / min, calcined for 2 hours, ground and crushed after cooling, and then washed twice with deionized water and freeze-dried for 10 hours to obtain tubular biomass carbon.
[0093] S1.2: 3 parts by weight of dicyandiamide and 2 parts by weight of nickel nitrate are dissolved in 300 parts by weight of ethanol solution, stirred at 78° C. for 5 hours, then 0.5 parts by weight of tubular biomass carbon are added, and stirring is continued for 24 hours to obtain a mixed solution;
[0094] S1.3: The mixed solution was placed in a quartz tube furnace, and the temperature was raised to 1000°C at 5°C / min in a nitrogen atmosphere, and the mixture was calcined and kept warm for 1 hour. The black product obtained by calcination was placed in a 7 mol / L sulfuric acid solution, and stirred at 80°C for 8 hours. The mixture was then washed with deionized water until neutral, and vacuum dried to obtain nitrogen-doped carbon nanotubes.
[0095] S1.4: immersing 2 parts by weight of nitrogen-doped carbon nanotubes in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:4, ultrasonically treating for 1 hour, and leaving at room temperature for 10 hours, then washing with deionized water until neutral, and vacuum drying at 80°C for 20 hours to obtain acidified nitrogen-doped carbon nanotubes;
[0096] S1.5: Add 1 mol / L KOH-ethanol solution to 3 parts by weight of 14 wt% perfluorosulfonic acid resin-ethanol dispersion, adjust the pH value of the resin dispersion to neutral, and obtain a perfluorosulfonic acid resin ethanol dispersion. Mix the acidified nitrogen-doped carbon nanotubes with the perfluorosulfonic acid resin ethanol dispersion in a mass ratio of 80:5, grind them in a mortar and grind them evenly. Then, transfer them to a tubular furnace filled with nitrogen and calcine them. Raise the temperature to 480°C at 5°C / min and keep them warm for 10 hours to obtain fluorinated carbon nanotubes.
[0097] S2: Preparation of positive electrode sheet
[0098] S2.1: Coronene and NDI-1 were mixed and dissolved in dichloroethane at a molar ratio of 1:1 to a concentration of 7 mg / mL. The mixed solution was divided into centrifuge tubes, set the speed to 11000 rpm, and centrifuged for 30 min. The precipitate was washed with anhydrous ethanol, collected and dried to obtain the co-crystal;
[0099] S2.2: 10 parts by weight of eutectic, 2 parts by weight of carbon black, 2 parts by weight of fluorinated carbon nanotubes and 2 parts by weight of polyvinylidene fluoride were mixed and ground for 10 minutes, the ground mixed powder was transferred to a beaker, 20 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 12 hours to form a slurry;
[0100] S2.3: Use a scraper to evenly apply the slurry on the aluminum foil, then put the aluminum foil into a vacuum drying oven at 90°C and dry it for 14 hours. After drying, the aluminum foil is sliced with a slicer to prepare a positive electrode sheet;
[0101] S3: Preparation of dendritic mesoporous silica nanoparticles
[0102] S3.1: 0.5 parts by weight of triethanolamine was added to 300 parts by weight of deionized water, and the mixture was heated to 80° C. and stirred for 30 minutes. Then, 8 parts by weight of cetyltrimethylammonium bromide and 5 parts by weight of sodium salicylate were added, and the mixture was stirred for 1 hour to obtain a mixed solution;
[0103] S3.2: 30 parts by weight of tetraethyl orthosilicate and 5 parts by weight of ethanol were mixed and added to the mixed solution, and the mixture was stirred for reaction for 3 hours, and then centrifuged at 2000 r / min for 10 minutes. The precipitate after centrifugation was washed twice with ethanol, and then calcined at 500° C. for 6 hours to obtain dendritic mesoporous silica nanoparticles;
[0104] S4: Preparation of two-dimensional hierarchical porous composites loaded with cerium oxide
[0105] S4.1: 0.2 parts by weight of dendritic mesoporous silica nanoparticles are dispersed in 12 parts by weight of ethanol, and then 0.3 parts by weight of zinc acetate dihydrate and 0.2 parts by weight of cerium nitrate hexahydrate are added, and the mixture is stirred and mixed at room temperature for 10 hours, and then evaporated at 40°C, and the obtained powder is calcined at 400°C for 3 hours to obtain a composite precursor;
[0106] S4.2: 0.5 parts by weight of 2-methylimidazole was dissolved in 12 parts by weight of deionized water, and ultrasonic dispersion was performed for 1 minute to obtain a 2-methylimidazole solution; 0.2 parts by weight of sodium dodecyl sulfate was dissolved in 12 parts by weight of deionized water, and ultrasonic dispersion was performed for 1 minute to obtain a sodium dodecyl sulfate solution;
[0107] S4.3: Add 1 part by weight of the composite precursor to the sodium dodecyl sulfate solution, then add the 2-methylimidazole solution, stir and mix for 10 seconds, seal the mixture in a strain bottle, react at 26°C for 20 hours, and then centrifuge at 7000 r / min to obtain a reaction product;
[0108] S4.4: washing the reaction product twice with methanol, then washing it twice with deionized water, and then keeping it in ethanol for 20 hours. Finally, drying the reaction product to obtain a two-dimensional hierarchical porous composite material loaded with cerium oxide;
[0109] S5: Preparation of negative electrode sheet
[0110] S5.1: 10 parts by weight of a two-dimensional hierarchical porous composite material loaded with cerium oxide, 4 parts by weight of carbon black, 2 parts by weight of fluorinated carbon nanotubes and 2 parts by weight of polyvinylidene fluoride were mixed and ground for 10 minutes, the ground mixed powder was transferred to a beaker, 20 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 12 hours to form a slurry;
[0111] S5.2: Use a scraper to evenly apply the slurry on the copper foil, then put the copper foil into a vacuum drying oven at 80° C. and dry it for 12 h. After drying, the copper foil is sliced with a slicer to prepare a negative electrode sheet;
[0112] S6: Assembly of lithium batteries
[0113] S6.1: The positive electrode sheet, the negative electrode sheet, and the Celgard2400 polymer separator are formed into a battery cell by using a Z-shaped stacking structure, wherein the positive and negative electrode tabs of the stack are located on the opposite sides of the battery cell, and the outermost circle of the stack body is terminated by the negative electrode sheets on the upper and lower sides of the battery cell body, thereby obtaining a battery cell body;
[0114] S6.2: The battery cell is prepared into a lithium-ion battery through the processes of baking, ultrasonic welding, top-side packaging, baking, injection of lithium hexafluorophosphate electrolyte, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0115] Example 3
[0116] A method for preparing a fast-charge and fast-discharge lithium battery, such as Figure 1 As shown, the following steps are included:
[0117] S1: Preparation of fluorinated carbon nanotubes based on biomass carbon
[0118] S1.1: The cattail fluff was washed with deionized water for 3 times, and then soaked in anhydrous ethanol for 30 min, and then dried in an oven at 120°C. 2 parts by weight of the dried cattail fluff was added to 230 parts by weight of 0.5 M H 3 PO 4 The solution was stirred for 2 hours and then allowed to stand for 25 hours. The supernatant was removed, and the precipitate was dried at 120°C, placed in a tubular furnace filled with nitrogen, and heated to 670°C at 8°C / min, calcined for 3 hours, cooled and ground, then washed with deionized water for 3 times, and freeze-dried for 12 hours to obtain tubular biomass carbon.
[0119] S1.2: dissolving 2 parts by weight of dicyandiamide and 1 part by weight of nickel nitrate in 250 parts by weight of ethanol solution, stirring at 80° C. for 8 hours, then adding 0.2 parts by weight of tubular biomass carbon, and continuing to stir for 25 hours to obtain a mixed solution;
[0120] S1.3: The mixed solution was placed in a quartz tube furnace, and the temperature was raised to 1100°C at 8°C / min in a nitrogen atmosphere, and the mixture was calcined and kept warm for 2 hours. The black product obtained by calcination was placed in a 5 mol / L sulfuric acid solution, and stirred at 85°C for 10 hours. The mixture was then washed with deionized water until neutral, and vacuum dried to obtain nitrogen-doped carbon nanotubes.
[0121] S1.4: immersing 1 part by weight of nitrogen-doped carbon nanotubes in a mixed solution of concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3, ultrasonically treating for 2 hours, and leaving at room temperature for 12 hours, then washing with deionized water until neutral, and vacuum drying at 90°C for 24 hours to obtain acidified nitrogen-doped carbon nanotubes;
[0122] S1.5: Add 1 mol / L KOH-ethanol solution to 2 parts by weight of 14 wt% perfluorosulfonic acid resin-ethanol dispersion, adjust the pH value of the resin dispersion to neutral, and obtain a perfluorosulfonic acid resin ethanol dispersion. Mix the acidified nitrogen-doped carbon nanotubes with the perfluorosulfonic acid resin ethanol dispersion in a mass ratio of 70:5, grind them in a mortar, and then transfer them to a tubular furnace filled with nitrogen for calcination, raise the temperature to 500°C at 8°C / min, and keep them warm for 12 hours to obtain fluorinated carbon nanotubes;
[0123] S2: Preparation of positive electrode sheet
[0124] S2.1: Coronene and NDI-1 were mixed and dissolved in dichloroethane at a molar ratio of 1:1 to a concentration of 6 mg / mL. The mixed solution was divided into centrifuge tubes, set the speed to 12000 rpm, and centrifuged for 40 min. The precipitate was cleaned with anhydrous ethanol, collected and dried to obtain the co-crystal;
[0125] S2.2: 8 parts by weight of eutectic, 1 part by weight of carbon black, 1 part by weight of fluorinated carbon nanotubes and 1 part by weight of polyvinylidene fluoride were mixed and ground for 12 minutes, the ground mixed powder was transferred to a beaker, 10 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 14 hours to form a slurry;
[0126] S2.3: Use a scraper to evenly apply the slurry on the aluminum foil, then put the aluminum foil into a vacuum drying oven at 90°C and dry it for 14 hours. After drying, the aluminum foil is sliced with a slicer to prepare a positive electrode sheet;
[0127] S3: Preparation of dendritic mesoporous silica nanoparticles
[0128] S3.1: 0.3 parts by weight of triethanolamine was added to 200 parts by weight of deionized water, and the mixture was heated to 85° C. and stirred for 40 minutes. Then, 5 parts by weight of cetyltrimethylammonium bromide and 3 parts by weight of sodium salicylate were added, and the mixture was stirred for 2 hours to obtain a mixed solution;
[0129] S3.2: 30 parts by weight of tetraethyl orthosilicate and 3 parts by weight of ethanol were mixed and added to the mixed solution, stirred for reaction for 4 hours, and then centrifuged at 3000 r / min for 12 minutes. The precipitate after centrifugation was washed with ethanol three times, and then calcined at 550° C. for 8 hours to obtain dendritic mesoporous silica nanoparticles;
[0130] S4: Preparation of two-dimensional hierarchical porous composites loaded with cerium oxide
[0131] S4.1: 0.15 parts by weight of dendritic mesoporous silica nanoparticles are dispersed in 10 parts by weight of ethanol, and then 0.2 parts by weight of zinc acetate dihydrate and 0.1 parts by weight of cerium nitrate hexahydrate are added, and the mixture is stirred and mixed at room temperature for 12 hours, and then evaporated at 45°C, and the obtained powder is calcined at 450°C for 5 hours to obtain a composite precursor;
[0132] S4.2: 0.3 parts by weight of 2-methylimidazole was dissolved in 10 parts by weight of deionized water, and ultrasonic dispersion was performed for 2 minutes to obtain a 2-methylimidazole solution; 0.1 parts by weight of sodium dodecyl sulfate was dissolved in 10 parts by weight of deionized water, and ultrasonic dispersion was performed for 2 minutes to obtain a sodium dodecyl sulfate solution;
[0133] S4.3: Add 0.5 parts by weight of the composite precursor to the sodium dodecyl sulfate solution, then add the 2-methylimidazole solution, stir and mix for 15 seconds, seal the mixture in a strain bottle, react at 28°C for 24 hours, and then centrifuge at 8000 r / min to obtain a reaction product;
[0134] S4.4: washing the reaction product with methanol for three times, then washing it with deionized water for three times, and then placing it in ethanol for 24 hours. Finally, drying the reaction product to obtain a two-dimensional hierarchical porous composite material loaded with cerium oxide;
[0135] S5: Preparation of negative electrode sheet
[0136] S5.1: 8 parts by weight of a two-dimensional hierarchical porous composite material loaded with cerium oxide, 3 parts by weight of carbon black, 1 part by weight of carbon nanotubes and 1 part by weight of polyvinylidene fluoride were mixed and ground for 12 minutes, the ground mixed powder was transferred to a beaker, 10 parts by weight of N-methylpyrrolidone was added under magnetic stirring, the beaker was sealed with a sealing film, and the mixture was stirred for 14 hours to form a slurry;
[0137] S5.2: Use a scraper to evenly apply the slurry on the copper foil, then put the copper foil into a vacuum drying oven at 90° C. and dry it for 14 h. After drying, the copper foil is sliced with a slicer to prepare a negative electrode sheet;
[0138] S6: Assembly of lithium batteries
[0139] S6.1: The positive electrode sheet, the negative electrode sheet, and the Celgard2400 polymer separator are formed into a battery cell by using a Z-shaped stacking structure, wherein the positive and negative electrode tabs of the stack are located on the opposite sides of the battery cell, and the outermost circle of the stack body is terminated by the negative electrode sheets on the upper and lower sides of the battery cell body, thereby obtaining a battery cell body;
[0140] S6.2: The battery cell is prepared into a lithium-ion battery through the processes of baking, ultrasonic welding, top-side packaging, baking, injection of lithium hexafluorophosphate electrolyte, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
[0141] Comparative Example 1
[0142] Compared with Example 1, the difference of Comparative Example 1 is that step S2.1 is removed in Comparative Example 1, and the eutectic in step S2.2 is replaced with an equal weight portion of lithium iron sulfate, and the remaining steps remain unchanged to prepare a lithium-ion battery, which is recorded as Comparative Example 1.
[0143] Comparative Example 2
[0144] Compared with Example 1, the difference of Comparative Example 2 is that, in Comparative Example 2, the fluorinated carbon nanotubes in step S2.2 are removed, and the other steps remain unchanged to prepare a lithium-ion battery, which is recorded as Comparative Example 2.
[0145] Comparative Example 3
[0146] Compared with Example 1, the difference of Comparative Example 3 is that Comparative Example 3 removes steps S3-S4, replaces the two-dimensional hierarchical porous composite material loaded with cerium oxide in step S5.1 with an equal weight portion of artificial graphite, and prepares a lithium-ion battery without changing the other steps, which is recorded as Comparative Example 3.
[0147] Comparative Example 4
[0148] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes steps S1.2-S1.5, replaces the fluorinated carbon nanotubes in steps S2.2 and S5.1 with tubular biomass carbon in equal weight portions, and prepares a lithium-ion battery without changing the remaining steps, which is recorded as Comparative Example 4.
[0149] Comparative Example 5
[0150] Compared with Example 1, the difference of Comparative Example 5 is that, in Comparative Example 5, the cerium nitrate hexahydrate in step S1.4 is removed, and the other steps remain unchanged to prepare a lithium ion battery, which is recorded as Comparative Example 5.
[0151] Comparative Example 6
[0152] Compared with Example 1, the difference of Comparative Example 6 is that Comparative Example 6 removes steps S3 and S4.1, replaces the composite precursor in step S4.3 with 0.2 parts by weight of zinc acetate dihydrate and 0.1 parts by weight of cerium nitrate hexahydrate, and prepares a lithium-ion battery without changing the other steps, which is recorded as Comparative Example 6.
[0153] Comparative Example 7
[0154] Compared with Example 1, the difference of Comparative Example 7 is that, in Comparative Example 7, steps S4.2-S4.3 are replaced by "dissolving 4 parts by weight of 2-methylimidazole in 13 parts by weight of methanol, stirring and mixing for 10 minutes, then adding 0.5 parts by weight of the composite precursor, ultrasonicating for 5 minutes, and then reacting at 60°C for 24 hours, and then centrifuging at 7000 r / min to obtain a reaction product", and the remaining steps remain unchanged to prepare a lithium-ion battery, which is recorded as Comparative Example 7.
[0155] Performance tests were performed on Examples 1-3 and Comparative Examples 1-7. The test results are shown in Table 1.
[0156] Table 1. Performance test results of Examples 1-3 and Comparative Examples 1-7
[0157]
[0158] In terms of safety performance, Examples 1-3 all meet the requirements of GB / T31485-2015.
[0159] It can be seen from the data of the embodiment in Table 1 that the lithium ion battery prepared by the present invention has excellent performance and is conducive to fast charging and discharging; the data of comparative examples 1 and 2 are lower than those of the embodiment, indicating that the addition of eutectic to the preparation of the positive electrode plate of the battery improves the ion transmission rate, thereby improving the charge and discharge performance of the battery, and the addition of fluorinated carbon nanotubes and eutectic can improve the capacity and cycle life of the electrode; the data of comparative examples 3 and comparative examples 5-7 are also lower than those of the embodiment, indicating that the two-dimensional hierarchical porous composite material loaded with cerium oxide is used for the preparation of the negative electrode plate to improve the ion transmission efficiency, improve the charge and discharge rate and cycle stability of the battery; the data of comparative example 4 is also lower than that of the embodiment, indicating that the addition of fluorinated carbon nanotubes doped with nitrogen atoms and fluorine atoms reduces the resistance in the ion transmission process, and lithium ions can move more quickly between the positive and negative electrodes, thereby improving the charge and discharge rate and power performance of the battery, which is conducive to fast charging and discharging of the battery.
[0160] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a fast-charge and fast-discharge lithium battery, characterized in that: The steps include: S1: Preparation of fluorinated carbon nanotubes based on biomass carbon Preparation of tubular biomass carbon by cattail fluff, followed by nitrogen doping of the tubular biomass carbon to obtain nitrogen-doped carbon nanotubes, acidification of the nitrogen-doped carbon nanotubes and subsequent fluorine doping to obtain fluorinated carbon nanotubes; S2: Preparation of positive electrode sheet A eutectic is prepared by coronene and NDI-1, and a positive electrode plate is prepared by using the eutectic, carbon black, fluorinated carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone as raw materials; S3: Preparation of dendritic mesoporous silica nanoparticles Dendritic mesoporous silica nanoparticles are obtained by a synthetic reaction using triethanolamine, hexadecyltrimethylammonium bromide, sodium salicylate, tetraethyl orthosilicate and ethanol as raw materials. S4: Preparation of two-dimensional hierarchical porous composites loaded with cerium oxide Dendritic mesoporous silica nanoparticles, zinc acetate dihydrate and cerium nitrate hexahydrate were mixed and calcined to prepare a composite precursor, and then a two-dimensional hierarchical porous composite material loaded with cerium oxide was prepared by regulating with a 2-methylimidazole solution and a sodium dodecyl sulfate solution; S5: Preparation of negative electrode sheet A positive electrode sheet is prepared by using a two-dimensional hierarchical porous composite material loaded with cerium oxide, carbon black, fluorinated carbon nanotubes, polyvinylidene fluoride and N-methylpyrrolidone as raw materials; S6: Assembly of lithium batteries Assembling a positive electrode sheet, a negative electrode sheet, a coated separator and an electrolyte to prepare a lithium battery; Step S2: Preparation of the positive electrode sheet, specifically comprising the following steps: S2.1: Coronene and NDI-1 were mixed and dissolved in dichloroethane at a molar ratio of 1:1 to a concentration of 6-7 mg / mL. The mixed solution was divided into centrifuge tubes, the speed was set to 11000-12000 rpm, and centrifuged for 30-40 min. The precipitate was cleaned with anhydrous ethanol, collected and dried to obtain the co-crystal; S2.2: 8-10 parts by weight of eutectic, 1-2 parts by weight of carbon black, 1-2 parts by weight of fluorinated carbon nanotubes and 1-2 parts by weight of polyvinylidene fluoride are mixed and ground for 10-12 minutes, the ground mixed powder is transferred to a beaker, 10-20 parts by weight of N-methylpyrrolidone is added under magnetic stirring, the beaker is sealed with a sealing film, and the mixture is stirred for 12-14 hours to form a slurry; S2.3: Use a scraper to evenly apply the slurry on the aluminum foil, then put the aluminum foil into a vacuum drying oven at 80-90°C and dry it for 12-14 hours. After drying, the aluminum foil is sliced with a slicer to prepare a positive electrode sheet; NDI-1 structure: 。 2. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 1, characterized in that: Step S1 is to prepare fluorinated carbon nanotubes based on biomass carbon, which specifically includes the following steps: S1.1: Wash the cattail fluff with deionized water for 2-3 times, soak the washed cattail fluff in anhydrous ethanol for 20-30 minutes, and then dry it in an oven at 110-120°C, add 2-3 parts by weight of the dried cattail fluff to 230-240 parts by weight of 0.5M H3PO4 solution, stir for 1-2 hours, and then stand for 24-25 hours, remove the supernatant, dry the precipitate at 110-120°C, place it in a tubular furnace filled with nitrogen, heat it to 650-670°C at 5-8°C / min, calcine it for 2-3 hours, grind it after cooling, and then wash it with deionized water for 2-3 times, freeze-dry it for 10-12 hours, and obtain tubular biomass carbon; S1.2: dissolving 2-3 parts by weight of dicyandiamide and 1-2 parts by weight of nickel nitrate in 250-300 parts by weight of ethanol solution, stirring at 78-80° C. for 5-8 hours, then adding 0.2-0.5 parts by weight of tubular biomass carbon, and continuing stirring for 24-25 hours to obtain a mixed solution; S1.3: placing the mixed solution in a quartz tube furnace, heating to 1000-1100°C at 5-8°C / min in a nitrogen atmosphere, calcining and keeping warm for 1-2h, placing the black product obtained by calcination in a 5-7mol / L sulfuric acid solution, stirring at 80-85°C for 8-10h, then washing with deionized water until neutral, and vacuum drying to obtain nitrogen-doped carbon nanotubes; S1.4: immersing 1-2 parts by weight of nitrogen-doped carbon nanotubes in the mixed solution, ultrasonicating for 1-2 hours, and leaving at room temperature for 10-12 hours, then washing with deionized water until neutral, and vacuum drying at 80-90° C. for 20-24 hours to obtain acidified nitrogen-doped carbon nanotubes; S1.5: Add 1 mol / L KOH-ethanol solution to 2-3 parts by weight of 14 wt% perfluorosulfonic acid resin-ethanol dispersion, adjust the pH value of the resin dispersion to neutral, and obtain a perfluorosulfonic acid resin ethanol dispersion. Mix the acidified nitrogen-doped carbon nanotubes with the perfluorosulfonic acid resin ethanol dispersion in a mass ratio of 70-80:5-30, grind them in a mortar and grind them evenly. Then transfer them to a tubular furnace filled with nitrogen and calcine them. Raise the temperature to 480-500°C at a rate of 5-8°C / min and keep them warm for 10-12h to obtain fluorinated carbon nanotubes.
3. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 2, characterized in that: Step S3: Preparation of dendritic mesoporous silica nanoparticles, specifically comprising the following steps: S3.1: adding 0.3-0.5 parts by weight of triethanolamine to 200-300 parts by weight of deionized water, heating to 80-85°C and stirring for 30-40 minutes, then adding 5-8 parts by weight of cetyltrimethylammonium bromide and 3-5 parts by weight of sodium salicylate, stirring and mixing for 1-2 hours to obtain a mixed solution; S3.2: Mix 30-40 parts by weight of tetraethyl orthosilicate and 3-5 parts by weight of ethanol, add the mixture to the mixed solution, stir and react for 3-4 hours, then centrifuge at 2000-3000 r / min for 10-12 minutes, wash the precipitate after centrifugation with ethanol 2-3 times, and then calcine at 500-550°C for 6-8 hours to obtain dendritic mesoporous silica nanoparticles.
4. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 3, characterized in that: Step S4 is the preparation of a two-dimensional hierarchical porous composite material loaded with cerium oxide, which specifically comprises the following steps: S4.1: Disperse 0.15-0.2 parts by weight of dendritic mesoporous silica nanoparticles in 10-12 parts by weight of ethanol, then add 0.2-0.3 parts by weight of zinc acetate dihydrate and 0.1-0.2 parts by weight of cerium nitrate hexahydrate, stir and mix at room temperature for 10-12 hours, then evaporate to dryness at 40-45° C., and calcine the obtained powder at 400-450° C. for 3-5 hours to obtain a composite precursor; S4.2: dissolving 0.3-0.5 parts by weight of 2-methylimidazole in 10-12 parts by weight of deionized water, and dispersing by ultrasonic for 1-2 minutes to obtain a 2-methylimidazole solution; dissolving 0.1-0.2 parts by weight of sodium dodecyl sulfate in 10-12 parts by weight of deionized water, and dispersing by ultrasonic for 1-2 minutes to obtain a sodium dodecyl sulfate solution; S4.3: Add 0.5-1 parts by weight of the composite precursor to the sodium dodecyl sulfate solution, then add the 2-methylimidazole solution, stir and mix for 10-15 seconds, seal the mixture in a strain bottle, react at 26-28°C for 20-24 hours, and then centrifuge at 7000-8000 r / min to obtain a reaction product; S4.4: The reaction product is washed with methanol for 2-3 times, and then washed with deionized water for 2-3 times, and then placed in ethanol for 20-24 hours. Finally, the reaction product is dried to obtain a two-dimensional hierarchical porous composite material loaded with cerium oxide.
5. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 4, characterized in that: Step S5: Preparation of the negative electrode sheet, specifically comprising the following steps: S5.1: 8-10 parts by weight of a two-dimensional hierarchical porous composite material loaded with cerium oxide, 3-4 parts by weight of carbon black, 1-2 parts by weight of carbon nanotubes and 1-2 parts by weight of polyvinylidene fluoride are mixed and ground for 10-12 minutes, the ground mixed powder is transferred to a beaker, 10-20 parts by weight of N-methylpyrrolidone is added under magnetic stirring, the beaker is sealed with a sealing film, and the mixture is stirred for 12-14 hours to form a slurry; S5.2: Use a scraper to evenly apply the slurry on the copper foil, then put the copper foil into a vacuum drying oven at 80-90°C and dry it for 12-14 hours. After drying, the copper foil is sliced with a slicer to prepare a negative electrode sheet.
6. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 5, characterized in that: Step S6: assembling the lithium battery, specifically comprising the following steps: S6.1: The positive electrode sheet, the negative electrode sheet, and the coated separator are formed into a battery cell by using a Z-shaped stacking structure, wherein the positive and negative electrode tabs of the stacking are located on the opposite sides of the battery cell, and the outermost circle of the stacking body is terminated by the negative electrode sheets on the upper and lower sides of the battery cell body, thereby obtaining a battery cell body; S6.2: The battery cell is prepared into a lithium-ion battery through the processes of baking, ultrasonic welding, top-side packaging, baking, injection of lithium hexafluorophosphate electrolyte, standing, pressure formation, aging, exhaust and secondary sealing, and capacity division.
7. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 2, characterized in that: The mixed solution in step S1.4 is obtained by mixing concentrated nitric acid and concentrated sulfuric acid in a volume ratio of 1:3-4.
8. The method for preparing a fast-charge and fast-discharge lithium battery according to claim 6, characterized in that: The coated membrane in step S6.1 is a Celgard 2400 polymer membrane.
9. A fast-charge and fast-discharge lithium battery, characterized in that: Prepared by the preparation method of a fast-charge and fast-discharge lithium battery as described in any one of claims 1-8.
Citation Information
Patent Citations
Preparation process of stable lithium electric core with high discharge capacity
CN110416520A
Decomposition of silicon-containing precursors on porous scaffold materials
CN116978701A